Desenvolvimento, produção e qualidade de ovos de poedeiras brancas e vermelhas submetidas a métodos de debicagem - Hítalo José Santos Barbosa (2019)
Two simultaneous experiments were conducted, one with white layers (Lohmann® White) and the other with brown layers (Lohmann® Brown), with the objective of evaluating the effects of beak trimming methods on development, production, hematological variables, organ weight, cloacal temperature, beak size and quality of eggs between the 1st to the 31st week of life of the birds. 900 birds were used in each experiment, distributed in a completely randomized design with three treatments, defined by the beak methods - Conventional, Infrared Radiation and Dutch - with five replications of 60 birds up to the 14th week. After 14 weeks, the design followed entirely at random and consisted of the same three treatments and with five replications of 24 birds each. In the experiment with the white line, in the evaluation of the total breeding period, the Dutch beak provided better feed conversion for the birds when compared with the other treatments (P ≤ 0.05). In the production phase, birds subjected to Dutch debeaking showed lower feed consumption, less weight gain, lower percentage of laying and lower egg mass when compared to birds subjected to debeaking by infrared radiation, with no difference from conventional beaking (P ≤ 0.05). In the egg quality analysis, conventional debeaking resulted in eggs with lower specific weight and Haugh units. The debeaking by infrared radiation had less relative weight on the gizzard + proventriculum in the 3rd week and greater relative weight of the liver in the 9th week of the birds' life (P ≤ 0.05). In the analysis of the lymphoid organs the weight of and the cloacal temperature, no differences were found in the ages evaluated (P > 0.05). The treatments influenced the size of the birds' beak (p ≤ 0.05), and the birds who subjected to Dutch debeaking, they had a beak size at 31 weeks of life. It was concluded that the Dutch beak trimming for it being more invasive, it harmed the initial performance with consequences in the production phase of the birds. In the second experiment with brown laying hens, birds subjected to Dutch debeaking showed better feed conversion during the total rearing period (P ≤ 0.05). There was no effect of treatments for the variables of egg production and quality evaluated (P > 0.05). The Dutch beak trimming provided the birds with a greater relative weight of the gizzard in the 1st week and a greater relative weight of the liver in the 3rd week of the birds' life (P ≤ 0.05). In the analysis of the lymphoid organs, there was a difference for the relative weight of the spleen in the 11th week where birds beaked by infrared radiation had the highest relative weight of this organ (P ≤ 0.05). Birds submitted to Dutch debeaking showed a smaller beak size at 31 weeks of life. It was concluded that Dutch beak trimming and infrared radiation are viable alternatives in contrast to conventional beak, without damage to the development, production and quality of brown la ying eggs.